2019
DOI: 10.1021/acs.jpcc.9b04493
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Photocatalytic Reduction of CO2 by Ag3PO4(111)/g-C3N4 Nanocomposite: A First-Principles Study

Abstract: Density functional Theory (DFT) calculations have been performed to investigate the electronic structure and photocatalytic activity of a hybrid Ag3PO4(111)/g-C3N4 structure. Due to Ag(d) and O(p) states forming the upper part of the valence band and C(p), N(p) and Ag(s) the lower part of the conduction band, the band gap of the hybrid material is reduced from 2.75 eV for Ag3PO4(111) and 3.13 eV for monolayer of g-C3N4 to about 2.52 eV, enhancing the photocatalytic activity of the Ag3PO4(111) surface and g-C3N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 64 publications
3
24
0
Order By: Relevance
“…In recent years, the amount of carbon dioxide (CO 2 ) in the atmosphere has increased due to the industrial revolution, in addition to the use of fossil fuels, as one of the major sources of energy in human life [1] . Carbon dioxide plays an important role in air pollution, global warming, and climate change, which causes many environmental problems such as moisturizing the air, damaging plants, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the amount of carbon dioxide (CO 2 ) in the atmosphere has increased due to the industrial revolution, in addition to the use of fossil fuels, as one of the major sources of energy in human life [1] . Carbon dioxide plays an important role in air pollution, global warming, and climate change, which causes many environmental problems such as moisturizing the air, damaging plants, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the amount of carbon dioxide (CO 2 ) in the atmosphere has increased due to the industrial revolution, in addition to the use of fossil fuels, as one of the major sources of energy in human life. [1] Carbon dioxide plays an important role in air pollution, global warming, and climate change, which causes many environmental problems such as moisturizing the air, damaging plants, etc.. [2] Therefore, the adsorption, activation, storage, and conversion of CO 2 into valuable products for environmental reasons has attracted the attention of many researchers. [3] Extensive researches have dealt with the conversion of CO 2 into alternative suitable hydrocarbon fuels such as methanol (CH 3 OH), methane (CH 4 ), formic acid (HCOOH), and formaldehyde (CH 2 O).…”
Section: Introductionmentioning
confidence: 99%
“…In another case, Tafreshi et al reported a Z-scheme Ag 3 PO 4 (111)/g-C 3 N 4 composite in the CO 2 photoreduction and illustrated the mechanism with the help of DFT studies and experiments. 121 The authors demonstrated the higher selectivity of CH 4 over CH 3 OH due to the thermodynamically favourable exothermic reaction (energy released: 2.43 eV for CH 4 and 1.18 eV for CH 3 OH). All the possible intermediates and corresponding products using multiple electron reduction processes and water oxidation are summarized in the mechanism in Fig.…”
Section: Key Factors Affecting Photocatalytic Co2 Reductionmentioning
confidence: 97%
“…Also, different products can be obtained by controlling surface structures, such as acid–base sites [ 76–78 ] and organic groups. [ 79,80 ] Since 2009, several new photocatalytic systems have been proposed gradually, including g‐C 3 N 4 , [ 81–90 ] CdS, [ 90–99 ] BiOCl, [ 100–102 ] and BiOIO 3 . [ 103 ] Synthetic strategies for various nano‐/microstructure were also developed, such as quantum dots (QDs), [ 104–106 ] nanowires (NWs), [ 107–109 ] nanosheets, [ 110–112 ] and heterostructures.…”
Section: Overview Of Photocatalysts For Co2 Reductionmentioning
confidence: 99%